Nematicidal Activity of Burkholderia arboris J211 Against Meloidogyne incognita on Tobacco - Zhang, Renjun; Ouyang, Jin; Xu, Xingyang; Li, Jie; Rehman, Muzammal; Deng, Gang; Shu, Jie; Zhao, Dake; Chen, Suiyun; Sayyed, R. Z.; Fahad, Shah; Chen, Yaqiong (Frontiers in Microbiology, 2022)
Root-knot nematode (Meloidogyne incognita) is the most widespread and damaging nematode affecting tobacco. Due to the lack of effective measures to control this nematode, its management can be achieved, using biocontrol agents. This study investigated in vitro efficacy of the antagonistic bacterial strain J211 isolated from tobacco rhizosphere soil against M. incognita, and further assessed its role in controlling nematodes, both in pot and field trials. Phylogenetic analysis of the 16S rRNA ribosomal gene sequence of strain J211 assigned to Burkholderia arboris. Culture filtrates B. arboris J211 exhibited a nematicidal activity against the second-stage juveniles (J2s) of M. incognita, with a 96.6% mortality after 24 h exposure. Inoculation of J211 in tobacco roots significantly reduced the root galling caused by M. incognita, both in pot and field trials. Meanwhile, B. arboris J211 also promoted tobacco growth and increase flue-cured tobacco yield by 8.7% - 24.3%. Overall, B. arboris J211 is a promising and alternative bionematocide, controlling root-knot nematodes efficiently and improving tobacco yield.